Improvement of country’s transport system and its regions through the digital transformation of the Russian transport industry - Pugachev, I. N.; Kazarbin, A. V. (Vestnik SibADI (Online), 2024)
Introduction. The prerequisite for the study of the problem was the Strategy for the spatial development of the country for the period until 2024, proposed by the President of the Russian Federation, the basis of which is transport infrastructure by mode of transport, ensuring the connectivity of settlements, requiring phased modernization, personnel, technical and technological support, digitalization and integration into one ecosystem of digital services both for individual modes of transport and in aggregate as a ‘single window’ for the state and business for all transportation. The subject of the research was the digital transformation of the transport sector using the example of the automobile and road complex as the most in demand and, in our opinion, receptive to the digital economy. Materials and methods. Currently, compatibility, coordination and interaction of various modes of transport are becoming important when performing multimodal transportation of goods and passengers using digital technologies and platform solutions. In other words, a unified digital platform of the transport complex must be created, which is a systemic basis for information interactions and unites all current and planned information and digital solutions based on agreed principles, rules and standards Results. The incomplete list of objects of digital transformation given in the article, due to its wide variety of systems necessary for use in transport, indicates its scale and adaptation to the needs of transport of existing achievements and new technical solutions in various fields. At the current stage, in order to solve the current problems, cooperation of industry scientific organizations is required, taking into account the main directions of their activities, current scientific, technical and personnel potential, integration with institutes of the Russian Academy of Sciences, scientific, design organizations and industrial enterprises of advanced high-tech and knowledge-intensive industries, with international scientific research. community. Conclusion. The methods and activities proposed in the article will ensure maximum efficiency and unity of the basic principles of the functioning and development of mobility systems in all regions and cities of the Russian Federation, will ensure an accelerated transition to the digital economy and the achievement of technological sovereignty of our country.